Building The Spirit of Independent Business Through The Manifestation of Islamic Entrepreneurship (Brain-Mouth-Muscle) - Hartanto, Selamet (AL-IKTISAB: Journal of Islamic Economic Law, 2018)
Building an independent business spirit is very important. This entrepreneurial spirit has its own strength in the face of intense competition in the global economy. Therefore, to strengthen the economy of the country in general and to strengthen the family economy in the area ofentrepreneurship should be encouraged. To build a spirit of independent business, many models that can be implanted in the soul of a person. Things that should not be abandoned are Islamic values. There are keywords that must be considered 3A, namely amanah, al-akhlak al-karimah, and al Qur'an. In the real entrepreneurship, a man is equipped by God with brain, talk and muscle as the basis for entrepreneurship maximally. Maximizing one of the three, humans are able to survive in entrepreneur contestation. Especially if the three are collaborated into a single unit and used maximally, then the results will also be the maximum and satisfactory.